Case study on virtual product lifecycle management with a PDM package - Koo, Chee Kit. (2008)
This study investigates the product lifecycle processes, enabling technologies and product data management (PDM) approaches to speed up information exchange, improve workflow, facilitate collaboration, and enable innovations among team members. A case study is focused on the system architecture, product data structure and processes of an implemented solution.